2023
DOI: 10.1101/2023.10.04.560907
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparison of short-read, HiFi long-read, and hybrid strategies for genome-resolved metagenomics

Raphael Eisenhofer,
Joseph Nesme,
Luisa Santos-Bay
et al.

Abstract: Shotgun metagenomics enables the reconstruction of complex microbial communities at a high level of detail. Such an approach can be conducted using both short-read and long-read sequencing data, as well as a combination of both. To assess the pros and cons of these different approaches, we used 22 faecal DNA extracts collected weekly for 11 weeks from two respective lab mice to study seven performance metrics over four combinations of sequencing depth and technology: i) 20 Gbp of Illumina short-read data, ii) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…PacBio HiFi sequencing produces highly accurate consensus reads (>Q20, median Q30) that are 10–20 kb in length (Wenger et al 2019). Several studies have demonstrated that HiFi sequencing generally produces more total MAGs and higher quality MAGs than short-read sequencing (Priest et al 2021; Gehrig et al 2022; Meslier et al 2022; Eisenhofer et al 2023; Orellana et al 2023; Tao et al 2023; Zhang et al 2023), and that HiFi sequencing outperforms ONT for metagenome assembly (Meslier et al 2022; Sereika et al 2022). The high accuracy of HiFi reads has led to the development of two new metagenome assembly methods, hifiasm-meta (Feng et al 2022) and metaMDBG (Benoit et al 2023), which perform better than previous methods such as HiCanu (Nurk et al 2020) and metaFlye (Kolmogorov et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…PacBio HiFi sequencing produces highly accurate consensus reads (>Q20, median Q30) that are 10–20 kb in length (Wenger et al 2019). Several studies have demonstrated that HiFi sequencing generally produces more total MAGs and higher quality MAGs than short-read sequencing (Priest et al 2021; Gehrig et al 2022; Meslier et al 2022; Eisenhofer et al 2023; Orellana et al 2023; Tao et al 2023; Zhang et al 2023), and that HiFi sequencing outperforms ONT for metagenome assembly (Meslier et al 2022; Sereika et al 2022). The high accuracy of HiFi reads has led to the development of two new metagenome assembly methods, hifiasm-meta (Feng et al 2022) and metaMDBG (Benoit et al 2023), which perform better than previous methods such as HiCanu (Nurk et al 2020) and metaFlye (Kolmogorov et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…in 2023 demonstrated the usefulness of combining both technologies thanks to their respective strengths (Eisenhofer et al, 2023;Orellana et al, 2023;Wick et al, 2023). In addition, the rapid evolution in single-cell sequencing promises to open new perspectives and deepen even further our knowledge of environmental microbiomes (Lloréns-Rico et al, 2022).…”
mentioning
confidence: 99%